The Tactics of the Search - Ioan Aron (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2023)
Among the factors that directly contribute to the success of a search, a central place is occupied by psychological factors, factors whose knowledge, by the judicial body, is absolutely necessary. The exact outline of the issue of psychology implies, from the very beginning, emphasizing the distinction between the psychology of the person conducting the search and the psychology of the searched. This distinction is imposed by the fact that we are in front of a procedural act, somewhat similar (of course on psychological grounds) to listening to the accused or the defendant. In this "duel", we can see that not only the criminal investigation body seeks to notice the way of thinking and behaviour of the searched person, but also the searched person, especially if he is a well-versed person, will try to put himself in the position of the person coming to search, when he hides the objects.